Unifying the criteria of elastic stability of solids - Wang, Hao; Li, Mo (Journal of physics. Condensed matter, 2012)
The elastic stability criterion formulated by Born is based on the convexity requirement of the equilibrium free energy F of a stress-free crystal under small strain fluctuation, that demands the elastic constant tensor C to be positive definite, |C| > 0. For a crystal subject to an external stress, Hill specifies that for the crystal to be stable, the difference between its internal energy change δE and the work done to the system δW must be positive, i.e. δE − δW > 0. Polanyi, Frenkel, and Orowan proposed a different stability criterion based on stress increment for a loaded system, τ( + Δ ) − τ( ) > 0 until the limit is reached at dτ d = 0. Although known empirically, the formal connection between the different criteria has not been established rigorously. Using finite deformation theory, we show quite simply that the different formulations of the stability criteria originate from the same necessary condition for the convexity of the free energy of the system subject to external loading, f = F − W. However, in practice caution must be taken in implementation of the different criteria; they may lead to quite different results, especially when stability bifurcation occurs.